2016
DOI: 10.3389/fneur.2016.00173
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 5-HT1F Receptors in Monkey Vestibular and Trigeminal Ganglion Cells

Abstract: BackgroundEvidence of serotonergic involvement in vestibular pathway contributions to migraine and balance disorders is compelling. Serotonergic 5-HT1B and 5-HT1D receptors are expressed extensively in inner ear ganglia of monkeys and rats. The serotonergic 5-HT1F receptor is also a target of triptans. This study describes its distribution in vestibular and trigeminal ganglia of monkeys.MethodsUsing primary polyclonal antibodies raised against oligopeptides specific for the human 5-HT1F receptor, neuronal soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…Messenger RNA (mRNA) for the 5-HT 1F receptor was found in human brain, uterine, and mesenteric tissue, but not in heart, kidney, liver, pancreas, spleen, or testes. In situ hybridization showed the presence of mRNA in the cerebral cortex, hippocampus, and dorsal raphe of guinea pig brains [60] and in the guinea pig and human TG [61][62][63]. In other studies, mRNA for 5-HT 1F was detected in human cerebral blood vessels [61], rat meningeal dura mater [64], cerebral cortex, and TG [65].…”
Section: -Ht 1f Receptor Locationmentioning
confidence: 99%
“…Messenger RNA (mRNA) for the 5-HT 1F receptor was found in human brain, uterine, and mesenteric tissue, but not in heart, kidney, liver, pancreas, spleen, or testes. In situ hybridization showed the presence of mRNA in the cerebral cortex, hippocampus, and dorsal raphe of guinea pig brains [60] and in the guinea pig and human TG [61][62][63]. In other studies, mRNA for 5-HT 1F was detected in human cerebral blood vessels [61], rat meningeal dura mater [64], cerebral cortex, and TG [65].…”
Section: -Ht 1f Receptor Locationmentioning
confidence: 99%
“…3-5 5-hydroxy tryptamine (5-HT) is a kind of important humoral mediator and neurotransmitter, and studies have revealed that 5-HT is closely related to the occurrence and development of migraine. [6][7][8] In addition, the studies on many subtypes of 5-HT have found that 5-HT receptor 6 (5-HTR6) bears a close relationship with the occurrence of pain. [9][10][11] Therefore, in this project, the VM patients were enrolled from our department to detect the polymorphism of 5-HTR6 rs770963777 site with the TaqMan-MGB probe and explore the correlation of 5-HTR6 gene polymorphism with VM, hoping to provide a theoretical support for the genetic polymorphism of VM.…”
Section: Introductionmentioning
confidence: 99%
“…Vestibular ganglion cells, like trigeminal ganglion cells, express 5‐HT 1B , 5‐HT 1D , and 5‐HT 1F receptors (Fig. ) . Ahn et al found that CGRP and 5‐HT 1F receptors colocalize in the vestibular nuclei .…”
Section: Discussion/observationsmentioning
confidence: 98%